2020
DOI: 10.3390/molecules25204829
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potential Chemical Probe as Inhibitors of CXCL12 Using Ligand-Based Virtual Screening and Molecular Dynamic Simulation

Abstract: CXCL12 are small pro-inflammatory chemo-attractant cytokines that bind to a specific receptor CXCR4 with a role in angiogenesis, tumor progression, metastasis, and cell survival. Globally, cancer metastasis is a major cause of morbidity and mortality. In this study, we targeted CXCL12 rather than the chemokine receptor (CXCR4) because most of the drugs failed in clinical trials due to unmanageable toxicities. Until now, no FDA approved medication has been available against CXCL12. Therefore, we aimed to find n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…During simulation, a slight enhancement in the Rg value of the 6LZG-POM complex was observed, indicating its structural integrity. The MD simulation results entirely support that POM forms stable complexes with 2OQ5 and 6LZG, indicating its inhibitory properties for the TMPRSS2 and ACE2-RBD receptor, respectively [ 60 ].
Fig.
…”
Section: Resultsmentioning
confidence: 85%
“…During simulation, a slight enhancement in the Rg value of the 6LZG-POM complex was observed, indicating its structural integrity. The MD simulation results entirely support that POM forms stable complexes with 2OQ5 and 6LZG, indicating its inhibitory properties for the TMPRSS2 and ACE2-RBD receptor, respectively [ 60 ].
Fig.
…”
Section: Resultsmentioning
confidence: 85%
“…The 3D pharmacophore model includes five primary common features, each of which represents: F1 = Don: Represents a donor group capable of donating hydrogen bonds during the drug-target interaction, 34 F2 = Acc: Denotes an acceptor group that can form hydrogen bonds with the target protein, 37 F3 = Aro: Signifies an aromatic ring, which often plays a crucial role in hydrophobic interactions and π-π stacking with the target protein, F4 = Aro: Another aromatic ring feature, emphasizing the significance of additional hydrophobic interactions in the drug-target binding, and F5 = Aro: The third aromatic ring feature, further highlighting the importance of multiple aromatic interactions in the pharmacophore model. 38 These five common features combine the essential aspects identified earlier during the pharmacophore model creation.…”
Section: Discussionmentioning
confidence: 85%
“…Root mean square fluctuation (RMSF) measures the magnitude of atomic deviations relative to their average positions, indicating the flexibility and local motion characteristics of the system [26]. From Figure 6B, it can be observed that, among the 392 amino acid residues, the mTyr protein exhibits higher RMSF values mainly in the peptide chain region of 240-300, indicating higher flexibility in that area.…”
Section: Simulationmentioning
confidence: 99%